Water quality of shallow tube wells as affected by sanitary latrines and groundwater flow - Rahman, Syed Hafizur; Fakhruddin, ANM; Uddin, Mohammed Jamal; Zaman, Md Shahid; Talukder, Asish; Adyel, Tanveer Mehedi; Sarker, Md Mizanur Rahman (Journal of Bangladesh Academy of Sciences, 2014)
The present study investigated the probable influence of latrines and groundwater flow on the water quality of shallow tube wells in Shinduria village (23?52' N and 90?14' E) of Dhaka district, Bangladesh. A questionnaire survey was made to collect basic information on tube wells and latrines. Four boreholes were drilled to investigate lithostratigraphy. Twenty one water samples were collected and their physico-chemical parameters (Dissolved Oxygen, pH, phosphate, sulphate, nitrate, nitrite and iron) were analyzed using standard method. Total viable bacterial count (TVBC), total coliform count (TCC), total faecal coliform count (TFCC), total salmonella shigella (TSS) and total vibrio count (TVC) were also made using membrane filtration method. Average depth of the tube wells was 120 ft and most of them were less then ten years old. About 85% latrines were ring slab type and about 50% of these were built during the last five years. From borehole data, a shallow aquifer was identified at a depth of hundred feet from where local people extract drinking water. Although most of the physico-chemical parameters of the tested samples were within the Department of Environment (DoE). But almost all of the tested samples failed to ensure the quality of acceptable level for drinking water recommended by World Health Organization (WHO) due to the presence of higher load of TVBC (5.07 × 10³ cfu/100 ml), TCC (8.44 × 103cfu/10 0ml), TFCC (5.16 × 10² cfu/100 ml) and TSS (1.10 × 103cfu/100 ml). Local geological conditions and proximity between tube well and latrine promoted bacterial transport towards tube well while groundwater flow direction from the adjacent Bangshi River influenced the phenomenon. DOI: http://dx.doi.org/10.3329/jbas.v37i2.17565 Journal of Bangladesh Academy of Scinces, Vol. 37, No. 2, 231-243, 2013